Decreased Retinal Vascular Density in Alzheimer’s Disease (AD) and Mild Cognitive Impairment (MCI): An Optical Coherence Tomography Angiography (OCTA) Study - Wang, Xi; Zhao, Qianhua; Tao, Rui; Lu, Huimeng; Xiao, Zhenxu; Zheng, Li; Ding, Ding; Ding, Saineng; Ma, Yichen; Lu, Zhaozeng; Xiao, Yiqin (Frontiers in Aging Neuroscience, 2021)
Background: To explore the retinal vascular density changes in Alzheimer's disease (AD) and mild cognitive impairment (MCI) patients using optical coherence tomography angiography (OCTA). Methods: We recruit 62 AD patients, 47 MCI patients, and 49 cognitively healthy controls (HC) in this study. All participants in the study received a comprehensive ophthalmological and neurological evaluation, including global cognitive screening, as well as the mini-mental status test (MMSE), and completed the following eye examinations: visual acuity(VA), intraocular pressure (IOP), examination WITH slit-lamp, fundus photography (Version 1.5.0.0, NIDEK CO, LTD) and Optical coherence tomography imaging (software ReVue version 2017.1.0.155, Optovue Inc, Fremont, CA, USA). The visual rating scales for atrophy and white matter lesion in MRI was evaluated for all the patients with AD and MCI. Results: In the AD patient group, the superficial vascular density in the superior, inferior and whole retina was 44.64±3.34,44.65±3.55, and 44.66±3.36, respectively. These values were 44.24±3.15, 43.72±3.16 and 44±3.07, respectively, in the MCI patient group. After multivariate analysis of the generalized linear model, adjustments for the confounding factors of sex, age, hypertension, diabetes and the quality index of OCTA image, the superficial vascular density in the AD and MCI patient groups was significantly lower than that in the HC group (P < 0.05): 46.94±2.04, 46.67±2.26, and 46.82±2.08, respectively. No difference in the area of the FAZ among the three groups was observed (AD group: 0.34±0.11 mm²; MCI group: 0.36±0.12 mm²; control group: 0. 33±0.12 mm², p>0.05).The ganglion cell complex (GCC) thickness, inner parafovea thickness, and peripapillary retinal nerve fiber layer (p-RNFL) thickness were associated with the superficial vascular density. We found no significant correlation between the global cognition (MMSE scores) or between the Fazekas score and retinal OCT angiogram flow density. Conclusion: The superficial vascular density in the AD and MCI patient groups was significantly lower than that in the HC group. Our findings suggest the retinal microvascular dysfunction occurred in MCI and AD.